Mapping the Development of Biological Sciences and Philosophical Thought: A Bibliometric Analysis of Global Research Trends - Aida Syifaul Fajriyah; Slamet Suyanto (Scientiae Educatia, 2025)
This study aims to map the development of research at the intersection of biological sciences and philosophical thought, and to identify prevailing global trends within this interdisciplinary field. A bibliometric analysis approach was employed, utilizing data systematically retrieved from the Scopus database. A total of 95 English-language publications issued between 2021 and September 2025 were analyzed using VOSviewer to examine keyword co-occurrence patterns and visualize conceptual relationships among research topics. The findings reveal twelve distinct thematic clusters representing the intellectual structure of the field, encompassing themes such as evolution, philosophy of biology, ethics, biotechnology, and environmental issues. Overlay and density visualization analyses further indicate that topics pertaining to biotechnology, human enhancement, and ethical implications have emerged as prominent and rapidly developing research trends within the contemporary literature. Collectively, these findings demonstrate that the relationship between biological sciences and philosophical thought continues to evolve dynamically in parallel with ongoing scientific and technological advancements. This study further underscores the growing importance of interdisciplinary collaboration between biological sciences and philosophy in addressing the conceptual, ethical, and societal challenges inherent in modern biological research, while simultaneously offering a strategic roadmap for prospective scholarly inquiry at this productive disciplinary interface.